Electrochemical sensor amplified with cellulose nanofibers/Fe3O4 composite to the monitoring of hydrazine as a pollutant in water and wastewater samples. (December 2022) - Deng, Zilong; Wu, Zixuan; Rokni, Hassan; Yin, Zihua; Lin, Junzhong; Zhang, Hongcai; Cheraghi, Somaye
Abstract: A quite swift and sensitive analytical instrument was designed in this work to detect and monitor hydrazine in various water and wastewater samples. The glassy carbon electrode (GCE) was amplified using cellulose nanofibers/Fe3 O4 composite (CNF–Fe3 O4 /NC) for monitoring hydrazine in the concentration range of 0.001 - 140 M with a superior detection limit of 0.5 nM. Results showed a diffusion control process for the oxidation of hydrazine at the surface of CNF–Fe3 O4 /NC/GCE. Under the optimum condition (pH=8.0), the oxidation current of hydrazine was improved by about 2.3 times and the oxidation potential was reduced by about 60 mV at the surface of CNF–Fe3 O4 /NC/GCE compare to unmodified GCE. A standard addition method was employed to assess CNF–Fe3 O4 /NC/GCE's capability for the detection of hydrazine in water and wastewater samples, and a recovery range of 97.6 % to 104.9 % was noted. Graphical abstract: Image 1 Highlights: Synthesis of nanocellulose nanofibers/Fe3 O4 nanocomposite as new catalyst. Electrochemical sensing of hdrazine in water samples. Modification of electrode with nanocellulose nanofibers/Fe3 O4  for fabrication of electrochemical sensor.